Highest Incidence Cancers Study: A Real Global Analysis: Global Highest Incidence Cancers Study - Lamiaa mohammed; Ashjan Mohammed Hussain; Abbas, Sura Mouaid; Tareq Hafdi Abdtawfeeq; Ibrahim, Nathier A. (Iraqi Journal of Cancer and Medical Genetics, 2025)
Background: According to World Health Organization publications, cancer arises from the transformation of normal cells into tumor cells in a multi-stage process that generally develops from a precancerous lesion to a malignant tumor. These changes result from the interaction between a person’s genetic factors and three categories of external factors: physical carcinogenic factors, chemical carcinogenic factors, and biological carcinogenic factors. The incidence of cancer increases sharply with age, and the accumulation of cancer risks is associated with the tendency for the effectiveness of cell repair mechanisms to decline as the person ages. This paper highlights the three main cancers that are most common in the world: female breast, prostate, and lung, accompanied by global statistical indicators by region. Material & Methods: Publications for the year 2024 on the incidence and mortality of the most common cancer diseases in global regions were used. A comparison was made by types of cancers by regions and finding their indicators, illustrated with graphs, for the three cancers. Results: The data analysis indicated that the mortality-to-incidence ratio (MIR) was lowest for female breast cancer (0.29), intermediate for prostate cancer (0.27), and highest for lung cancer (0.73). While Asia had the highest incidence of the three cancers, Africa demonstrated the highest mortality in relation to incidence. Conclusion: The results of the analysis of the data of the three most prevalent cancers showed that in the developed countries, despite the high number of cancer cases, their deaths were the least due to the sound health environment and the availability of diagnostic and treatment factors, unlike the continent of Africa, their death rate was the highest among other continents, despite the low prevalence.